Economic Essence of Institutional Investors - R. O. Voskanian (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article investigates the economic essence of institutional investors in 2 aspects: distinction from individual investors and impact on finance stability. Within the frames of the 1st aspect arguments are provided to prove the fact that the key difference between institutional investors and individual ones is the recipient of investment returns. To study the 2nd aspect Russian and overseas academic literature is analyzed, as well as acute statistics that help classify institutional investors by three categories: proportion of the share capital, investment horizon and source of capital building-up. This classification forms a basis of identifying after-effects of realizing various investors’ right to withdrawal and their impact on finance stability. The author assumes that institutional investor can be ascribed simultaneously to different types, which can increase their influence on finance stability at the expense of combining possible effects of realizing the right to withdraw. It became clear that today minority investors do not exercise serious impact on finance stability, however, they can intensify the impact of majority shareholders (especially institutional investors) on corporate sector of finance market in drag-along and tag-along conditions.